Cryptomoschatone D2 from Cryptocarya mandioccana: cytotoxicity against human cervical carcinoma cell lines - M.P. Giocondo; C.L. Bassi; M. Telascrea; A.J. Cavalheiro; V.S. Bolzani; D.H.S. Silva; D. Agustoni; E.R. Mello; C.P. Soares (São Paulo State University (UNESP), 2009)
Among the substances isolated from Cryptocarya sp, some styrylpyrones, such as goniothalamin, demonstrate antiproliferative activity in a broad range of human cell lines. In the present study, we assessed the cytotoxicity of a styrylpyrone (cryptomoschatone D2), isolated from Cryptocarya mandiocanna, in HPV-infected (HeLa and SiHa) and uninfected (C33A) human cervical carcinoma cell lines and a human lung fibroblast line (MRC-5). The cytotoxicity was tested by the MTT assay. In this assay, cells were treated with cryptomoschatone D2 at 15, 30, 60 or 90 µM for 6, 24 or 48 hours, as well as for 6 hours followed by a post-treatment recovery period of 24, 48 or 72 hours. High cytotoxicity (dose- and timedependent) was observed in HeLa, SiHa, C33A and MRC-5 cell lines. Although in general the styrylpyrone cytotoxicity was not significantly different among the cell lines tested, it was apparently stronger in HeLa and C33A than in MRC-5 and SiHa in the 24 or 48-hour treatments. Moreover, HeLa and SiHa were able to recover their ability to proliferate, in direct proportion to the post-treatment recovery time. On the other hand, C33A did not demonstrate a similar post-treatment recovery. We can conclude that cryptomoschatone D2 possesses high dose-dependent or time-dependent cytotoxicity.